2018
DOI: 10.1002/anie.201808332
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Lithosilicates: Renaissance of a Reputable Substance Class with Surprising Luminescence Properties

Abstract: A hitherto unknown synthetic access to alkali lithosilicates, a substance class first described by Hoppe in the 1980s, is reported. With the synthesis and characterization of NaK7[Li3SiO4]8, a new representative has been discovered, expanding the family of known alkali lithosilicates. Astonishingly, NaK7[Li3SiO4]8 and the already established alkali lithosilicates Na[Li3SiO4] as well as K[Li3SiO4] display unforeseen luminescence properties, when doped with Eu2+. Na[Li3SiO4]:Eu2+ exhibits an ultra‐narrow blue, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 25 publications
2
54
0
2
Order By: Relevance
“…Dutzler SiO 4 ], and NaK 7 [Li 3 SiO 4 ] 8 with ultranarrowb lue, broadband, andy ellow-green double-band emission, respectively,w hen doped with Eu 2 + . [9] Independently, Sato et al reported the same compound Na[Li 3 SiO 4 ]:Eu 2 + with slightly different emission spectra. [10] Zhao et al reported furthermore the cyan emitting compound Na 0.5 K 0.5 [Li 3 SiO 4 ]:Eu 2 + [11] and green-emitting RbLi[Li 3 SiO 4 ] 2 :Eu 2 + .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dutzler SiO 4 ], and NaK 7 [Li 3 SiO 4 ] 8 with ultranarrowb lue, broadband, andy ellow-green double-band emission, respectively,w hen doped with Eu 2 + . [9] Independently, Sato et al reported the same compound Na[Li 3 SiO 4 ]:Eu 2 + with slightly different emission spectra. [10] Zhao et al reported furthermore the cyan emitting compound Na 0.5 K 0.5 [Li 3 SiO 4 ]:Eu 2 + [11] and green-emitting RbLi[Li 3 SiO 4 ] 2 :Eu 2 + .…”
Section: Introductionmentioning
confidence: 99%
“…Dutzler et al. published Na[Li 3 SiO 4 ], K[Li 3 SiO 4 ], and NaK 7 [Li 3 SiO 4 ] 8 with ultranarrow blue, broadband, and yellow‐green double‐band emission, respectively, when doped with Eu 2+ . Independently, Sato et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that purely oxide‐based species, crystallizing in structures closely related to the U[Cr 4 C 4 ]‐structure type, also tend to form promising phosphors upon doping with Eu 2+ . For example, Na[Li 3 SiO 4 ]:Eu 2+ and NaK 7 [Li 3 SiO 4 ] 8 :Eu 2+ both crystallize in the tetragonal space group I 4 1 / a , while K[Li 3 SiO 4 ]:Eu 2+ crystallizes in the triclinic space group P 1 . Both space groups are, as mentioned before, well known to comprise some of the most promising nitride based phosphors.…”
Section: Introductionmentioning
confidence: 89%
“…[24] Crystals of the solid-solution series with low x-values can be excited with near-UV light (λ exc = 365 nm) possessing a similar excitation spectrum like Na[Li 3 SiO 4 ]:Eu 2+ . [12] With a higher degree of substitution, the excitation slightly shifts towards blue light, while NELSAON shows an excitability from the near UV to the blue spectral region, which enables the usage in blue pumped pc-LEDs (Figure 4, right). All samples showed no degradation of the luminescence, even after storing them at ambient conditions for more than half a year.…”
Section: Luminescencementioning
confidence: 99%
See 1 more Smart Citation